Direct characterization of functional materials by haptenized fluorescent dendrimers for in vitro allergic drug diagnose - Ruiz-Sanchez, Antonio Jesus; Collado-Martín, Daniel; Mayorga Mayorga, Cristobalina; Torres-Jaén, María Josefa; Pérez-de-Inestrosa-Villatoro, Ezequiel (My University, 2020)
β-lactams are the most widely drug prescribed against infections, but they are the most commonly reported medication allergy too. A correct diagnosis of these allergic reactions is crucial to avoid rejecting them by other more expensive broad-spectrum antibiotics, with potential risk factors for the development of multiple drug-resistant bacteria. [1] Skin testing is the most consensual approach to diagnose β-lactam allergy, but this in vivo test is not risky free and should be performed under strict hospital surveillance.[2] In vitro testing is not still widely used on account of their low sensitivity. We report the use of already haptenized fluorescent dendrimers [3] to control the preparation of materials for in vitro test, and their verification by testing on patient sera samples. This fluorescent dendrimer is obtained from a dye with two orthogonal functional groups suitable for click chemistry. [4] Acknowledgments: This work was supported by: MINECO CTQ2016-75870P, Andalusian Regional Ministry Health (PI-0250-2016); European Regional Development Fund and “Plan Propio Universidad de Málaga” (UMA-Andalucía-TECH).
Keywords: Dendrímeros; Alergia a los medicamentos; Dendrimer; Michel's addition; Allergic drug